Penguins as bioindicators of mercury contamination in the southern Indian Ocean: geographical and temporal trends. (June 2016) - Carravieri, Alice; Cherel, Yves; Jaeger, Audrey; Churlaud, Carine; Bustamante, Paco
Abstract: Penguins have been recently identified as useful bioindicators of mercury (Hg) transfer to food webs in the Southern Ocean over different spatial and temporal scales. Here, feather Hg concentrations were measured in adults and chicks of all the seven penguin species breeding in the southern Indian Ocean, over a large latitudinal gradient spanning Antarctic, subantarctic and subtropical sites. Hg was also measured in feathers of museum specimens of penguins collected at the same sites in the 1950s and 1970s. Our aim was to evaluate geographical and historical variations in Hg transfer to penguins, while accounting for feeding habits by using the stable isotope technique (δ 13 C, habitat; δ 15 N, diet/trophic level). Adult feather Hg concentrations in contemporary individuals ranged from 0.7 ± 0.2 to 5.9 ± 1.9 μg g −1 dw in Adélie and gentoo penguins, respectively. Inter-specific differences in Hg accumulation were strong among both adults and chicks, and mainly linked to feeding habits. Overall, penguin species that feed in Antarctic waters had lower feather Hg concentrations than those that feed in subantarctic and subtropical waters, irrespective of age class and dietary group, suggesting different Hg incorporation into food webs depending on the water mass. While accounting for feeding habits, we detected different temporal variations in feather Hg concentrations depending on species. Notably, the subantarctic gentoo and macaroni penguins had higher Hg burdens in the contemporary rather than in the historical sample, despite similar or lower trophic levels, respectively. Whereas increases in Hg deposition have been recently documented in the Southern Hemisphere, future monitoring is highly needed to confirm or not this temporal trend in penguins, especially in the context of actual changing Hg emission patterns and global warming. Highlights: Feather Hg levels were measured in 7 penguin species from the southern Indian Ocean. Species and feeding habits were key determinants of both adult and chick Hg levels. Antarctic species had lower Hg burdens than subantarctic and subtropical ones. Some subantarctic species had higher Hg burdens today than in the 1970s. Future Hg evaluation is needed in lower trophic level biota from the Southern Ocean. Abstract : Feather Hg concentrations were measured in 7 penguin species from different sites and epochs in the Southern Ocean, revealing high and likely increasing Hg levels in subantarctic penguins.